Investigation of Flap Dimensional Parameters to Improve Hydrodynamic Performance of Oscillating Wave Surge Converter Device - Anggara, Rizki Aldi; Julian, James; Wahyuni, Fitri; Purba, Riki Hendra; Toding Bunga, Nely (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2025)
Renewable energy transition is a strategic step in overcoming environmental damage due to fossil fuel exploitation. Ocean wave energy comes with its popularity, considering its advantages in supplying energy continuously and having high energy density. Therefore, technology that can extract other wave energy effectively and efficiently is needed. This study focuses on identification flap geometry to improve the oscillating wave surge converter (OWSC) hydrodynamic performance. Through a numerical approach, the Boundary Element Method (BEM) is applied in three-dimensional flap modeling to accommodate testing the characteristics and performance of the OWSC device. This study identified five different samples: geometry 1, geometry 2, geometry 3, geometry 4, and geometry 5. The results show that the second geometry variation is the most optimal flap dimension parameter. The best proportion is found in the dimensional characteristics parallel to the elevation of the ocean waves to maximize the output torque. Overall, the second geometry performs satisfactorily with an average maximum power achievement of 41.52 Watts at a wave period of T = 1.5s. In addition, the OWSC device with this variation can work at an expansive wave period interval with a maximum CWR efficiency achievement of up to 52.14%.